Local and landscape‐level floral resources explain effects of wildflower strips on wild bees across four European countries. Issue 5 (15th July 2015) - Scheper, Jeroen; Bommarco, Riccardo; Holzschuh, Andrea; Potts, Simon G.; Riedinger, Verena; Roberts, Stuart P. M.; Rundlöf, Maj; Smith, Henrik G.; Steffan‐Dewenter, Ingolf; Wickens, Jennifer B.; Wickens, Victoria J.; Kleijn, David; et al.
Summary Growing evidence for declines in wild bees calls for the development and implementation of effective mitigation measures. Enhancing floral resources is a widely accepted measure for promoting bees in agricultural landscapes, but effectiveness varies considerably between landscapes and regions. We hypothesize that this variation is mainly driven by a combination of the direct effects of measures on local floral resources and the availability of floral resources in the surrounding landscape. To test this, we established wildflower strips in four European countries, using the same seed mixture of forage plants specifically targeted at bees. We used a before–after control–impact approach to analyse the impacts of wildflower strips on bumblebees, solitary bees and Red List species and examined to what extent effects were affected by local and landscape‐wide floral resource availability, land‐use intensity and landscape complexity. Wildflower strips generally enhanced local bee abundance and richness, including Red‐listed species. Effectiveness of the wildflower strips increased with the local contrast in flower richness created by the strips and furthermore depended on the availability of floral resources in the surrounding landscape, with different patterns for solitary bees and bumblebees. Effects on solitary bees appeared to decrease with increasing amount of late‐season alternative floral resources in the landscape, whereas effects on bumblebees increased with increasing early‐season landscape‐wide floral resource availability. Synthesis and applications. Our study shows that the effects of wildflower strips on bees are largely driven by the extent to which local flower richness is increased. The effectiveness of this measure could therefore be enhanced by maximizing the number of bee forage species in seed mixtures, and by management regimes that effectively maintain flower richness in the strips through the years. In addition, for bumblebees specifically, our study highlights the importance of a continuous supply of food resources throughout the season. Measures that enhance early‐season landscape‐wide floral resource availability, such as the cultivation of oilseed rape, can benefit bumblebees by providing the essential resources for colony establishment and growth in spring. Further research is required to determine whether, and under what conditions, wildflower strips result in actual population‐level effects.